Adaptation luminance simulation for CIE mesopic photometry system implementation. (February 2016) - Uchida, T; Ayama, M; Akashi, Y; Hara, N; Kitano, T; Kodaira, Y; Sakai, K
A simulation method to determine adaptation luminance is proposed for implementation of the CIE mesopic photometry system. The simulation takes four factors into account: luminance distribution, eye movement of observers, surrounding luminance effect and area of measurement. Each factor is modelled as a two-dimensional geometrical function. The method determines an adaptation luminance for the area of measurement through four calculation steps. The simulation method was applied to examples of luminance distributions of outdoor lit scenes and the results were compared with possible simple predictors of adaptation luminance. The comparisons suggest that the average luminance of the area of measurement can be considered as a good approximation in most of the cases. Exceptions are scenes for pedestrians in which there are many bright sources surrounding the area of measurement.